A discourse analysis of teachers' messages in official and unofficial WhatsApp groups - Hussein, Suzan Farouq F.; Rashid, Radzuwan Ab; Azizan, Mazlin; Alali, Omar Mohammad Mousa (Frontiers in Communication, 2023)
The present study concentrates on Jordanian English language teachers' social and discursive practices online. It represents an initial attempt to tackle the social media phenomenon in the professional life of teachers in Jordan. Also, discourse among teachers as faculty members in WhatsApp groups has not been thoroughly researched. Employing an ethnographic approach, this paper examines the differences in teachers’ discursive behaviour in official and unofficial WhatsApp groups. This exploratory study aims to scrutinise the way Jordanian English Language teachers at a Jordanian University construct their posts in the WhatsApp groups. Data generated through participant observations were analysed using discourse analysis and combined with a discursive psychology approach.¬ The findings provide novel insights into their professional discourse on the same platform (i.e. WhatsApp) with a different audience. This paper concludes that teachers behave differently in how they talk to their superiors than in how they speak to their colleagues to construct their desired identities. They convey a positive impression to their leaders, and they tend to use persuasive techniques to appear more friendly to others. The impression management techniques used are mainly exemplification, ingratiation and self-promotion.